Predictors of financial competence of Peruvian high school students in PISA 2022 - Bazán-Ramírez, Aldo; Hernández-Padilla, Eduardo; Palomino-Malpartida, Ybar Gustavo; Bazán-Ramírez, Wilfredo; Félix-Benites, Edwin (Frontiers in Education, 2025)
IntroductionThe financial literacy and competencies of future citizens are of global interest to educational researchers and behavioral scientists. We investigated the influence of academic achievement, financial literacy and sociodemographic factors on the Peruvian students’ financial competence performance in the Programme for International Student Assessment (PISA) 2022.MethodsData from 4,092 students were analyzed using multilevel hierarchical models. Five groups of predictor variables were evaluated: sociodemographics, financial familiarity and experience, financial literacy, support and involvement, and math and reading achievement.ResultsEight variables had independent significant effects on financial competencies: gender, technological resources and household possessions, attitudes to financial matters, familiarity with financial concepts, school financial education, family support and influence of friends. However, when testing a full multivariate model incorporating all predictor groups, math and reading achievement emerged as the strongest predictors of financial competence, followed by familiarity with financial concepts.DiscussionThe results suggest that the development of financial competencies in Peruvian students is more closely linked to general academic performance in mathematics and reading than to specific financial literacy variables. These findings have significant implications for educational policies and curriculum development, because starting in 2024, economic and financial contents were included in the Peruvian national curriculum.